The EffeCT of Pre-Questioning Technique on Students’ Reading Comprehension - Asih Rosnaningsih; Wulandari Wulandari (Journal of English Language Studies, 2017)
The objective of the study is to find out whether there is a significant effect of pre-questioning technique on students reading comprehension. In this research, the researcher used the quantitative research with the type of quasi-experimental research. This research involving two classes, VIII 8 was experiment class and VIII 9 was controlled class. VIII 8 was taught by using pre-questioning technique, while VIII 9 was taught by using conventional teaching. The researcher gave pre-test and post-test to the class. The collected data in this research are analyzed by using t-test. According to the result of statistical calculation, The result of pre-test, t-count was 0,32 < 1,987or accept H0 while in post-test, t-count was 2,293 > 1,987 or accept H1with 5% of significant level. It can be concluded that there is significant different effect of reading comprehension using pre-questioning technique between experiment and control class.Keyword: pre-questioning technique, quasi-experimental research, reading comprehension